Digital electrooptic modulators synthesized from directional couplers - Mohd. Supa'at, Abu Sahmah; Mohammad, Abu Bakar; Mohd. Kassim, Norazan (2001)
This paper presents an electrooptic digital modulator synthesized from cascaded directional coupler. For the digital modulator, a nearly perfect cross state and bar state can be obtained in a broad range of modulation voltages that is from O.031t to O.281t Volts.